PSVIII-35 Isolation and identification of lactic acid bacteria in guinea grass silages. (7th December 2018) - Otoni, I; Paula, R; Alves, J; Roseira, J; Pimentel, F; Ribeiro, K; Pereira, O
Abstract: The objectives of this study were to isolate and identify lactic acid bacteria (LAB) in guinea grass ( Panicum maximum Jacq. cultivar Mombasa) silage harvested in the summer (February) and winter (August) of 2017, at 60 and 122 days of regrowth, respectively. The grass was chopped into 1.5 cm particle size and ensiled in bags measuring 25.4 × 35.56 cm. The bags were stored at room temperature and triplicate bags were opened after 1, 3, 7, 14, 28, 56, and 90 days of fermentation. The 16s rRNA gene sequences were obtained by pre-selecting cells grown in 5 mL MRS broth at 37 ºC for 18 h. The 16S rRNA sequences that showed similarity equal to or greater than 97% were considered of the same Operational Taxonomic Unit. A total of 366 strains (170 in the summer and 196 in the winter) belonging to 21 different LAB species were isolated. The following species were identified: Enterococcus canintestini (1.27%), E. faecium (0.55%), E. gallinarum (2.19%), E. saccharolyticus (0.27%), Lactobacillus brevis (7.92%), L. buchneri (0.27%), L. coryniformis (0.27%), L. curieae (0.27%), L. hordei (0.55%), L. mali (3.28%), L. pantheris (4.10%), L. paracasei (10.38%), L. plantarum (24.04%), Lactococcus garvieae (0.55%), L. lactis (5.19%), Leuconostoc mesenteroides (6.01%), Leuconostoc pseudomesenteroides (1.37%), Pediococcus pentosaceus (26.23%), Weissella confusa (1.09%), W. oryzae (0.27%), and W. paramesenteroides (3.83%). Of these, only Lactobacillus brevis, L. plantarum, and Lactococcus lactis were common to both grass growing seasons. At 56 days of fermentation, Pediococcus pentosaceus (60%) and Lactobacillus pantheris (32%) were the predominant LAB species in summer and winter, respectively. On the last day of fermentation, P. pentosaceus (100%) and L. paracasei (28%) were the dominant species in the respective seasons. Greater heterogeneity of species was observed in the winter period.